2019
DOI: 10.1039/c8sc04747b
|View full text |Cite
|
Sign up to set email alerts
|

211At-labeled immunoconjugate via a one-pot three-component double click strategy: practical access to α-emission cancer radiotherapeutics

Abstract: A facile synthesis of an 211At-labeled immunoconjugate for α-emission therapy was achieved based on a one-pot three-component double click method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 47 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…19 This issue does not exists in the case of astatine since electrophilic astatine cannot react with tyrosines or histidines unless very drastic conditions are applied. [20][21][22] Similarly, the one-step approach based on boron clusters which provides improved in vivo stability of radiolabelling, but can dramatically alter antibody biodistribution (Scheme 1d), 23,24 is also not applicable to radioiodination since it requires the electrophilic halogen species that may, again, react with tyrosines and histidine residues.…”
Section: Introductionmentioning
confidence: 99%
“…19 This issue does not exists in the case of astatine since electrophilic astatine cannot react with tyrosines or histidines unless very drastic conditions are applied. [20][21][22] Similarly, the one-step approach based on boron clusters which provides improved in vivo stability of radiolabelling, but can dramatically alter antibody biodistribution (Scheme 1d), 23,24 is also not applicable to radioiodination since it requires the electrophilic halogen species that may, again, react with tyrosines and histidine residues.…”
Section: Introductionmentioning
confidence: 99%
“…Astatine-211 ( 211 At), a radionuclide with potential for TAT, is not covered in the scope of this review because of the markedly different chemistry of astatine compared with radiometals. [5,6] Actinium Actinium has three naturally occurring radionuclides. Actinium-227 ( 227 Ac, t 1/2 21 years) is the longest-lived isotope of actinium and constitutes almost all naturally occurring actinium.…”
Section: Review Reviewmentioning
confidence: 99%
“…As a result, azaelectrocyclization for lysine-selective conjugation (later coined as the RIKEN click reaction 9 -11 ) has become a standard technique heavily utilized in our research today. As shown in Figure 2B, we first began to prepare the aldehyde probe directly linked with molecules of interest via amide linkage� [12][13][14][15][16][17][18] To simplify the operation of the RIKEN click reaction, we transitioned to using another reaction to link the molecules� This has led to the preparation of RIKEN click reagents modified with groups such as a azide (for Staudinger ligation) 19 , dibenzocyclooctyne (for strain-promoted azidealkyne cycloaddition) 20,21 , and trans-cyclooctene (for tetrazine ligation) [22][23][24][25][26][27][28][29][30][31][32][33][34][35] � Numerous successfully applied molecules for protein modification clearly prove the versatility of the RIKEN click reaction. For instance, molecular imaging and radiotherapeutic applications have seen the usage of metal chelating agents, such as DOTA 12,13,18,20,30 , NOTA 20,30 , and closo-decaborate 21 .…”
Section: Therapeutic In Vivo Synthetic Chemistrymentioning
confidence: 99%
“…Moreover, the fluorescent imaging studies have utilized various fluorophores like coumarin 12,14,15 , NBD 14,18 , TAMRA 12,13,17,23,30 ,Cy5 13,18,19 , Hilyte Fluor 750 16 , fluorescein 23 , and FRET pairs 24 � Other molecules that have also found significant usage in our research include the conjugation of biotin 17,19,22 , and numerous types of complex N-glycans 19,22-34 � In terms of conjugates done using the RIKEN click reagent, our studies have shown applicability to various amine-containing scaffolds. A number of peptides and proteins have been conjugated under in vitro conditions; such as the cRGDyK peptide 22,24,30 , somatostatin 12,14,22 , albumin, orosomucoid 12 , and asialoorosomucoid 12 � This has also been extended to dendrimer complexes 18 , as well as a number of antibodies that include anti-GFP mAb 12 , anti-IGSF4 mAb 20 , and trastuzumab 21 � For example, the rapid rate of the RIKEN click reaction has also been beneficial for the preparation of radiotherapeutic agents 20,21 . To approach it, a onepot reaction can be performed the RIKEN click reagent, a tetrazine-linked metal chelator, and a targeting antibody (Fig.…”
Section: Therapeutic In Vivo Synthetic Chemistrymentioning
confidence: 99%